Respostas
respondido por:
2
12/4 = 36/12
a1 = 4 q =
3 an = a1.q^n-1
an = 4*3^n-1
an = 4^1. 3^n-1
Nota : 1 + n - 1 = n an = 4.3^n
a1 = 4 q =
3 an = a1.q^n-1
an = 4*3^n-1
an = 4^1. 3^n-1
Nota : 1 + n - 1 = n an = 4.3^n
respondido por:
0
Resposta:12/4 = 36/12
a1 = 4 q =
3 an = a1.q^n-1
an = 4*3^n-1
an = 4^1. 3^n-1
Nota : 1 + n - 1 = n an = 4.3^n
Explicação passo-a-passo: Eu fiz e acertei
Perguntas similares
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás
10 anos atrás
10 anos atrás